2004
DOI: 10.1002/pssa.200303975
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of AgIn5S8 and CuIn5S8 thin films

Abstract: Spinel AgIn 5 S 8 and CuIn 5 S 8 materials are perspective for application in optoelectronic semiconductor devices. For the first time, thin films of these compounds were grown and investigated. The films were deposited by a sequential process on Mo-coated soda lime glass. This process consists of sulphur vapour sulphurization of a metallic alloy precursor. We found that a good adhesion to the substrate (Mo-coated glass) could be achieved by introduction of a Ti layer between the substrate and the spinel layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…becomes in the (3 1 1) direction. These preferable (1 1 1), (4 2 0) and (3 1 1) orientations of the as-grown, thermally annealed at 450 and 600 K, respectively, agree well with our previous reported data for thin film and single crystal [4,7], with that reported for AgIn 5 S 8 thin films grown by the pulsed laser deposition technique [3], with that reported for films grown by the spray technique [8], and with that reported for grown by the sulphurization of Ag-In alloy films in sulphur vapour [5,9].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…becomes in the (3 1 1) direction. These preferable (1 1 1), (4 2 0) and (3 1 1) orientations of the as-grown, thermally annealed at 450 and 600 K, respectively, agree well with our previous reported data for thin film and single crystal [4,7], with that reported for AgIn 5 S 8 thin films grown by the pulsed laser deposition technique [3], with that reported for films grown by the spray technique [8], and with that reported for grown by the sulphurization of Ag-In alloy films in sulphur vapour [5,9].…”
Section: Resultssupporting
confidence: 92%
“…One of these ternary semiconductors is the compound AgIn 5 S 8 , which have attracted considerable attention [1][2][3][4][5][6]. AgIn 5 S 8 thin films have been fabricated by the pulsed laser deposition [3], thermal vacuum evaporation [4], vapour phase deposition [5], and spray pyrolysis [6] techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficiency of about 9.1% was associated with the p-CuInS 2 /CuI/nCuIn 5 S 8 tandem structure solar cell [8]. A variety of physical and chemical techniques have been employed to fabricate this material [11][12][13]. Among these methods, electrodeposition as a cheap and facile method is widely used for the co-deposition of copper indium sulfide thin films under particular conditions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…AgIn 5 S 8 thin films are attracting considerable attention [1][2][3][4][5][6][7][8] due to their technological applications. It has been shown that the photosensitive AgIn 5 S 8 /(InSe, GaSe) heterojunctions can be fabricated using bulk crystals grown from the melt and from the vapor phase or polycrystalline thin films of the ternary compound.…”
Section: Introductionmentioning
confidence: 99%